Does the Punitive Need the Supportive? A Sympathetic Critique of Current Grammars of Urban Injustice. Issue 4 (13th December 2012) - DeVerteuil, Geoff
<x xml:space="preserve">Abstract</x> Abstract: This paper is a sympathetic critique of mainstream grammars of urban injustice, arguing that they are frequently too one‐sided and selective to adequately grasp the full complexity of urban realities. Most prominently, I contend that urban injustice and punitiveness co‐exist with, if not sometimes depend upon, more supportive responses within urban space. I therefore counterbalance the spectacular logics of punitive urbanism and the everyday logics of control with a tripartite approach to logics assembled within the urban voluntary sector (abeyance, care and survival) as a way to reconnect to a broader set of practices. Two case studies are used to illustrate these contentions.